RISK OF ENVIRONMENTAL HEALTH RISK PARAMETERS NO2 AND COMPLAINTS OF RESPIRATION ON PUBLIC TRANSPORTATION DRIVERS (NEW CAMPUS-CITY) IN KENDARI CITY: RISKS OF ENVIRONMENTAL HEALTH - Asri Manafia; Erwin Azizi Jayadipraja; Ridwan Adi Surya (STIKes Mandala Waluya Kendari, 2021)
Background:For Kendari City, the NO2 concentration in the air measured on Jl.Abdullah Silondae street still below the quality standard. However, the NO2 concentration has increased and decreased based on the results of air monitoring from the Environment and Forestry Service regarding the Air Quality Index which is measured 2 times a year with NO2 parameters in 2017, the first measurement is the value obtained of 1.58 µg / m3 and the second measurement. amounting to 1.57 µg / m3. In 2018 the NO2 value in the first measurement was 4.2 µg / m3 and the second measurement was 5.23 µg / m3. Whereas in 2019 the NO2 value in the first measurement was 5.8 µg / m3 and in the second measurement was 3.8 µg / m3. Methods:This type of research is descriptive quantitative (Field Research and Laboratory Research). The population is the total number of public transportation and the number of drivers for the Baru-Kota Rayon 02 route, amounting to 154 public transportation units and 154 public transport drivers with the male gender. The samples are some of the public transport drivers for the New Kampus-Kota rayon 02 route. Results:Nitrogen dioxide (NO2) measurements were obtained96.85 µg / Nm3, 108.79 µg / Nm3 and 100.83 µg / Nm3 for 3 different locations. The highest respiratory complaints were cough symptoms for 47 people and the lowest was shortness of breath as many as 8 people. Conclusion:Risk management is carried out by reducing exposure time, planting trees that can absorb air pollution, maintaining endurance, limiting the age of motor vehicles and using environmentally friendly fuels.